DETERMINATION OF COMMUNITY STRUCTURE AND INDEX MANGROVE HEALTH INDEX (MHI) IN DELI SERDANG DISTRICT, PROVINCE NORTH SUMATRA - dea lusiyanti; Yudi Antomi; Triyatno Triyatno; Azhari Syarief (Remote Sensing Technology Study Program, 2023)
This research aims to 1) Know the structure of the mangrove community in Deli Serdang Regency, 2) To find out the differences in the classification of the health level of the mangrove communities in Deli Serdang Regency using Sentinel 2A and Landsat 8OLI imagery in 2022. In determining the structure of the mangrove community carried out by making plot plots to measure trunk circumference and types of mangroves found in Deli Serdang Regency, while to find out differences in the classification of mangrove health levels it was done by comparing the vegetation density values ​​in the field and the canopy density values ​​based on the NDVI vegetation index from Sentinel 2A and Landsat 8OLI imagery. year 2022. The results of this study are, 1) The dominant mangrove species in Deli Serdang Regency are the Avicennia marina, Avicennia alba and Excoecaria agallocha types, with a low level of species diversity. 2) Sentinel 2A imagery is better to use than Landsat 8OLI imagery in determining the Mangrove Health Index (MHI).